Hubungan Keaktifan Dan Motivasi Terhadap Pembelajaran Online Pada Mahasiswa - Wahyudha Tri Setiyoaji; Rais Muktamar Amin; Maria Claudia Sodakain; Endang Purwaningsih; Parno Parno (Department of Physics Education, Universitas Mataram, 2021)
Government policy on online learning as an effort to prevent the transmission of the spread of COVID-19 in schools, especially in classrooms. Therefore, this policy creates social restrictions and the exclusion of face-to-face learning systems and will temporarily be replaced by online learning through several digital platforms that have been selected by the teacher and each school. The purpose of this study was to determine the relationship between Activeness and Motivation on Online Learning in Students. This research uses quantitative and qualitative approaches, researchers distribute questionnaires in the form of google form. Based on the results of research on the relationship of online learning to student learning activeness and motivation in the activeness category, 64% who answered YES and 36% answered no respectively. In the category of motivation, it shows that 78.5% answered YES and 21.5% answered NO. Based on these results, it can be seen that activeness and motivation can influence students in online learning.